Características clínicas e epidemiológicos associadas ao uso da contenção mecânica numa unidade psiquiátrica do interior do Rio Grande do Sul - Mosele, Pedro Henrique Canova (2020)
Mechanical restraint (MR) is a procedure used in psychiatric units and emergencies with the aim of handling, mainly, episodes of aggression and agitation that are not responsive to other interventions. Even when correctly indicated and performed, it has been associated with the risk of clinical and psychological complications. Factors associated with the use of the MR vary widely among health services, and can support techniques that prevent its necessity. Hospital Universitário de Santa Maria (HUSM) does not yet have studies that aim to identify such factors. OBJECTIVES: To investigate the association of clinical and epidemiological factors of patients in psychiatric hospitalization at HUSM with the use of mechanical restraint to manage aggressive behavior. METHODOLOGY: A database generated from an observational, longitudinal, prospective and naturalistic study conducted between August 2012 and January 2013 was analyzed. Patients were interviewed at the Psychiatric Emergency Room (PS-PSIQ) and at the Paulo Guedes Unit (UPG) of HUSM. Demographic and clinical information were collected on admission. The Brief Psychiatric Rating Scale (BPRS) was applied at admission and at discharge. The Overt Aggression Scale (OAS) was scored daily. Data distribution occurred in a non-normal way. Bivariate analysis of categorical variables was performed using Fisher's exact test. Quantitative variables were assessed transversely by the Mann-Whitney test and longitudinally by the Wilcoxon test. RESULTS: Among the 1625 patients evaluated at the PS-PSIQ during the study period, 137 participants were selected. Adult inpatients were included, and patients with delirium were excluded. Among the participants, 27% required mechanical restraint throughout the study. The contained patients had a higher score on the BPRS scale at admission and on the OAS scale throughout hospitalization. Both contained and non-contained patients achieved general improvement in symptoms throughout hospitalization. The contained patients showed no change in the score of the Affect and Negative Symptoms domains of the BPRS scale during hospitalization. CONCLUSION: The determination of a profile of greater hetero-aggressiveness and psychopathological severity among the patients contained can collaborate with the use of early management techniques to prevent the need of MR at HUSM. The longitudinal analysis of the evolution of symptoms contradicts the hypothesis in the literature that MR could cause the onset or worsening of anxious and depressive symptoms. The present study corroborates the correct indication and use of MR as a way of protecting the patients and those close to them.